Examining the Role of Supply Chain Management in the Relationship between Management Control Systems and Hotel Performance - I Putu Hendra Martadinata; Lucy Sri Musmini; I Gusti Ngurah Agung Dananjaya (Universitas Negeri Yogyakarta, 2026)
This study aims to examine the role of supply chain management (SCM) in the relationship between management control systems (MCS) and hotel performance. Data were collected from four- and five-star hotels in Badung Regency, Bali, yielding 103 samples. The hypotheses were tested using a mediation analysis approach with bootstrapping. The findings indicate that MCS has a positive and significant effect on hotel performance. MCS also shows a positive but relatively weak influence on SCM, implying that supply chain practices are not entirely determined by internal control mechanisms. Furthermore, SCM positively and significantly affects hotel performance. However, SCM does not mediate the relationship between MCS and hotel performance, indicating that both variables contribute directly and independently to hotel performance. These results suggest that MCS and SCM function as independent yet complementary mechanisms to enhance hotel performance rather than operate within a mediated structure. The findings contribute to literature development by supporting the contingency perspective, indicating that the structural relationships among managerial systems are context-dependent and influenced by industry characteristics. Practically, the study highlights the importance of strengthening both control systems and supply chain practices to improve performance, particularly in highly competitive tourism destinations such as Bali.